In Vitro Comparison of Gutta-Percha Removal with H-File and ProTaper with or without Chloroform - Khalilak, Zohreh; Vatanpour, Mehdi; dadresanfar, Bahareh; Moshkelgosha, Pouneh; Nourbakhsh, HamidReza (Iranian Endodontic Journal, 2013)
Introduction: Removal of root filling materials is one of the key steps in success of root canal retreatment. The purpose of this study was to evaluate the efficacy of H-File and ProTaper with or without chloroform in the removal of gutta-percha during retreatment of mandibular premolars. Materials and Methods: Sixty mandibular premolars with one canal, and curvatures less than 30 degrees were used in this experimental study. They were instrumented with K-files and laterally obturated with condensed gutta-percha using AH26 as the sealer and were stored in 100% humidity at 37°C for 2 weeks. The teeth were randomly divided into four groups of 15 teeth each. Removal of gutta-percha was performed with H-File and ProTaper. All techniques were used with or without chloroform. The teeth were split longitudinally and the area of remaining gutta-percha/sealer on the root canal wall was explored under stereomicroscope. Retreatment time duration was also recorded for each sample. Data were analyzed statistically by Two-way ANOVA, t-test and Tukey’s. Results: In all groups, no significant difference was found in remaining gutta-percha and sealer with or without using chloroform, but chloroform shortened the time of retreatment. ProTaper left significantly less remaining filling materials than H-File (P<0.05). Retreatment time was significantly different between the studied groups (P<0.001). Conclusion: ProTaper Ni-Ti instruments proved to be more efficient and time-saving devices for removal of gutta-percha compared to H-File in canals with no or slight curvature.